Ferreting out blast disease resistance in advanced breeding lines of rice (Oryza sativa) by phenotypic evaluation and microsatellite markers - BHATT, J P (The Indian Journal of Agricultural Sciences, 2018)
Rice (Oryza sativa L.) is the second most important cereal crop of developing countries and the staple food of about 65% of the world's population. Rice blast is a serious disease affecting rice, caused by a fungal pathogen Magnaporthe grisea (anamorph - Pyricularia grisea). In this endeavor, it is important to identify durable resistance sources. Forty two elite advanced breeding lines containing local and IRRI cultivars in their parentage were screened for the blast disease in uniform blast nursery during wet season of 2012 and 2013 using local land race Pankhali-203 as an inoculum spreader. Four elite lines, viz. GR-7/CRMAS-2231-36(8-4-1-1-1), GR-7/DDR-8(1-5-1-1), IR-28/IET-16804(4-1-1-1-1,2) and Jaya/IR-64(52-2-3-2) and GR-7, a released cultivar, were found highly resistant. Screening of these lines was also done using gene specific eighteen SSR markers. All markers amplified a total of 757 bands with an average of 42.10 bands per marker. The SSR marker RM535 for Pib gene and RM28050 for Pi20 gene produced maximum number (19) of alleles. Most of the breeding lines were found to have all the resistance genes with a diversity of allele range. The diversity analysis revealed the clustering pattern of these genotypes based on their parentage and not the genes present. The highest similarity index value of 0.53 was found between GR-7/NWGR-2002(3-1-1-1-1) and GR-7/NWGR-2002(2-3-1-2-1). Thus, present study revealed the resistance source for rice blast disease from advanced breeding lines simultaneously with the resistance genes present in them.